THE INFLUENCE OF SERVICE QUALITY AND CONSUMER SATISFACTION ON PURCHASE DECISIONS: A CASE STUDY OF NAIL ART SERVICES AT GLOSSE NAIL STUDIO - Mely Anggraini; Riswan (PT. Jurnal Center Indonesia Publisher, 2026)
The beauty service industry has experienced rapid growth in recent years, particularly in specialized services such as nail art. In a highly competitive market, service quality and consumer satisfaction are considered critical factors influencing purchase decisions. This study aims to analyze the influence of service quality and consumer satisfaction on consumer purchase decisions at Glosse Nail Studio. This research employs a quantitative approach using a survey method. Data were collected from customers of Glosse Nail Studio through structured questionnaires. Service quality is measured using dimensions adapted from SERVQUAL, including tangibles, reliability, responsiveness, assurance, and empathy. Consumer satisfaction is measured based on customers’ overall evaluation of service performance, while purchase decision is assessed through indicators reflecting consumer intention and actual buying behavior. Data analysis was conducted using multiple linear regression with the assistance of SPSS software, including validity and reliability tests, classical assumption tests, t-tests, F-tests, and coefficient of determination (R²). The results indicate that service quality has a positive and significant effect on consumer purchase decisions. Furthermore, consumer satisfaction also significantly influences purchase decisions. Simultaneously, service quality and consumer satisfaction significantly affect purchase decisions, indicating that higher perceived service performance leads to greater customer satisfaction and ultimately strengthens purchasing decisions.